The relationship between muscular strength and dance injuries: a systematic review - Moita, João Paulo (2022)
BACKGROUND: The physical demands placed on dancers put them at significant risk for injury, with rates similar to ones sustained by athletes in sports at the same level of performance. Muscle strength has been suggested to play a preventative role against injury in dancers. OBJECTIVE: To systematically search and examine the available evidence on the protective role of muscle strength in dance injuries. METHODS: Five electronic databases and two dance-specific science publications were screened up to September 2015. Study selection was based on a priori inclusion criteria on the relation between muscle strength components and injuries. Methodologic quality and level of evidence were assessed using the Downs and Black (DB) checklist and the Oxford Centre of Evidence- Based Medicine (OCEBM) 2011 model. RESULTS: From 186 titles found, only 8 studies met the inclusion criteria and were considered for review. Because of the significant heterogeneity of the included studies, meta-analysis was deemed inappropriate. The DB quality assessment results ranged from 18.7% to 75% (mean 42.3±16.9) and the OCEBM between 2b and 4. Some level 2b evidence from 2 studies suggested that pre-professional ballet dancers who get injured exhibit lower overall muscle strength scores on the lower extremity, and that lower extremity power gains may be associated with decreased bodily pain but not injury rate. CONCLUSIONS: Although there might be an association trend toward low muscle strength and dance injuries, the nature of that relation remains unclear, and presently the state of knowledge does not provide a solid basis for designing interventions for prevention.